2011
DOI: 10.1021/ed101186n
|View full text |Cite
|
Sign up to set email alerts
|

Lorenzo’s Oil as a Vehicle for Teaching Chemistry Content, Processes of Science, and Sociology of Science in a General Education Chemistry Classroom

Abstract: The film Lorenzo’s Oil depicts the challenges faced by the parents of a child with adrenoleukodystrophy, a neurological disorder that, they were told, was certainly fatal. The film contains a significant amount of chemistry, including concepts of fatty acid metabolism, enzyme inhibition, and the purification of substances. The film also raises important issues associated with “who does science?” and “who decides what science is done?” Those sociological issues are important in engaging nonscience majors in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…With regard to using movie clips, our research has shown that the audience will stay with the instructor even when digging quite deeply into chemical details because they want to know whether the movie got it right. , Other studies have found it useful to use entire movies and documentaries. For instance, movies based on true stories, such as Apollo 13 , October Sky , and Lorenzo’s Oil are able to drive discussions about lithium hydroxide carbon dioxide scrubbers, rocket fuel comparisons, and orphan disease patient advocacy, respectively. Likewise, we found that General Chemistry students were more motivated to write 600-word reports and did a better job when we used the biographical movie Dr. Ehrlich’s Magic Bullet or the documentary Me & Isaac Newton as source material instead of newspaper articles . The goal of the present study was to determine whether the documentary An Inconvenient Truth could meet the challenge of introducing the topic of climate change to students in a nonscience chemistry course.…”
mentioning
confidence: 83%
“…With regard to using movie clips, our research has shown that the audience will stay with the instructor even when digging quite deeply into chemical details because they want to know whether the movie got it right. , Other studies have found it useful to use entire movies and documentaries. For instance, movies based on true stories, such as Apollo 13 , October Sky , and Lorenzo’s Oil are able to drive discussions about lithium hydroxide carbon dioxide scrubbers, rocket fuel comparisons, and orphan disease patient advocacy, respectively. Likewise, we found that General Chemistry students were more motivated to write 600-word reports and did a better job when we used the biographical movie Dr. Ehrlich’s Magic Bullet or the documentary Me & Isaac Newton as source material instead of newspaper articles . The goal of the present study was to determine whether the documentary An Inconvenient Truth could meet the challenge of introducing the topic of climate change to students in a nonscience chemistry course.…”
mentioning
confidence: 83%
“…7 The orphan-disease movie Lorenzo's Oil (1992) provides students with enough context to promote deep explorations of the ethics of clinical trials, doctor−patient interactions, and persistence in the face of insurmountable odds. 8 In our own research, we found general chemistry students were more motivated to write 600-word reports and did a better job when we used Dr. Ehrlich's Magic Bullet (1940) or Me & Isaac Newton (1999) as source material instead of newspaper articles. 9 In that same paper, we describe 10 other similarly useful movies, each with different chemical and social themes.…”
mentioning
confidence: 86%
“…Apollo 13 (1995) and October Sky (1999) have been identified for their ability to drive discussions about lithium hydroxide carbon dioxide scrubbers, rocket fuel comparisons, model rocket propellants, payload calculations, and persistence of effort in the face of setbacks. , Jurassic Park (1993) was used to drive discussions about cloning, protein structure, DNA structure, molecular biology, and scientific ethics . The orphan-disease movie Lorenzo’s Oil (1992) provides students with enough context to promote deep explorations of the ethics of clinical trials, doctor–patient interactions, and persistence in the face of insurmountable odds . In our own research, we found general chemistry students were more motivated to write 600-word reports and did a better job when we used Dr. Ehrlich’s Magic Bullet (1940) or Me & Isaac Newton (1999) as source material instead of newspaper articles .…”
mentioning
confidence: 99%
“…The teaching of science through fiction has been previously explored. For example, Brown et al argue for the use of Captain America to “set the pedagogical stage” of the courses . Jack Stocker put forth the chemical nature of a number of classical science fiction stories to make the connections between fiction and reality readily available for educators .…”
Section: Introductionmentioning
confidence: 99%